Seismicity of the Neom megaproject area, Northwestern Saudi Arabia - Hassan Alzahrani (Elsevier, 2022)
A new seismicity map has been developed for Neom megaproject in the north-western zone of Saudi Arabia which has experienced considerable earthquake activity in the historical and recent times. The data used an up-to-date earthquake (Mw ≥ 3.0) catalog, major structures and tectonic trends. The majority of earthquake epicenters along the Red Sea rift are clustered in an axial trough, as well as on or nearby the active transform faults within the Red Sea basin. These earthquake activities are produced due to to the geodynamic processes such as continental rift and seafloor spreading prevailing in the area. Ten seismotectonic source zones have been identified in the area under investigation. It is indicated that the Gulf of Aqaba and southern end of the Gulf of Suez seismotectonic source zones are the most hazardous zone for Neom megaproject according to the maximum expected magnitudes where Mw are 7.7 and 6.7 respectively. Based on the magnitude-frequency relationship, the b-value varies from 0.41 to 0.934. The highest b values are related to the northwestern coast of the Red Sea, whereas the lowest b-value are related to the Duba source zone. Consequently, damaging earthquakes could affect Neom megaproject, so earthquake hazard assessment is highly recommended for the minimization and mitigation of earthquake losses in this area.